2011
DOI: 10.1182/blood-2011-02-337907
|View full text |Cite
|
Sign up to set email alerts
|

Serum hepcidin: reference ranges and biochemical correlates in the general population

Abstract: To date, concentrations of the promising biomarker hepcidin have only been assessed in serum of relatively small series of healthy volunteers and patients. We assessed age-and sex-stratified reference ranges of serum hepcidin concentration in a selected reference set and performed regression analyses to study associations between hepcidin and (biochemical) variables in a large, wellphenotyped sample of the general population (n ‫؍‬ 2998). All participants filled out a questionnaire on lifestyle, health status,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
242
16
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(306 citation statements)
references
References 42 publications
37
242
16
11
Order By: Relevance
“…Meanwhile, hepatic hepcidin expression was also enforced in OVX mice, relative to SHAM mice, indicating restrained iron absorption and iron egress in response to hepcidin-induced FPN degradation. In parallel to the findings from the current animal study, recent clinical investigations also identified increased serum hepcidin concentrations in postmenopausal women, relative to premenopausal women [64,65]. To this end, the induction of FPN was compensated by the increase of hepcidin in the absence of estrogen in mice.…”
Section: Discussionsupporting
confidence: 83%
“…Meanwhile, hepatic hepcidin expression was also enforced in OVX mice, relative to SHAM mice, indicating restrained iron absorption and iron egress in response to hepcidin-induced FPN degradation. In parallel to the findings from the current animal study, recent clinical investigations also identified increased serum hepcidin concentrations in postmenopausal women, relative to premenopausal women [64,65]. To this end, the induction of FPN was compensated by the increase of hepcidin in the absence of estrogen in mice.…”
Section: Discussionsupporting
confidence: 83%
“…The results from the current study are consistent with an epidemiological observation, demonstrating that serum hepcidin is higher in postmenopausal women than premenopausal women (Galesloot et al, 2011). The mechanism underlying the increased hepcidin expression upon estrogen deficiency has not been recognized thus far.…”
Section: Elevated Hepcidin Expression In Liver Devoid Of Endogenous Esupporting
confidence: 91%
“…However, the additive value of hepcidin over ferritin in the diagnosis of ID is yet questionable, since ferritin was the most important predictor of hepcidin at all times of measures. This is similar to results reported in previous studies in both children and adults (8,12). Furthermore, differences in ferritin between infants with and those without ID at the age of 4 mo were present already at the age of 1 wk, whereas no differences were observed in hepcidin concentrations at that age.…”
Section: Articlessupporting
confidence: 81%